2012
DOI: 10.1088/0953-2048/25/11/112002
|View full text |Cite
|
Sign up to set email alerts
|

A trapped field of >3 T in bulk MgB2fabricated by uniaxial hot pressing

Abstract: A trapped field of over 3 T has been measured at 17.5 K in a magnetised stack of two discshaped bulk MgB 2 superconductors of diameter 25 mm and thickness 5.4 mm. The bulk MgB 2 samples were fabricated by uniaxial hot pressing, which is a readily scalable, industrial technique, to 91% of their maximum theoretical density. The macroscopic critical current density derived from the trapped field data using the Biot-Savart law is consistent with the measured local critical current density. From this we conclude th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 30 publications
1
50
0
1
Order By: Relevance
“…This infiltration process does not require an external pressure to be applied to the reacting material and still produces highly dense final products [7]. It has been shown that MgB 2 bulk magnets could be used at 20 K [8][9][10][11]. High critical current density (J c ) and good homogeneity are essential for high trapped field magnets.…”
Section: Introductionmentioning
confidence: 99%
“…This infiltration process does not require an external pressure to be applied to the reacting material and still produces highly dense final products [7]. It has been shown that MgB 2 bulk magnets could be used at 20 K [8][9][10][11]. High critical current density (J c ) and good homogeneity are essential for high trapped field magnets.…”
Section: Introductionmentioning
confidence: 99%
“…The typical trapped field in bulk superconductors (> 3 T in bulk MgB 2 [1][2][3][4] or > 17 T in bulk (RE)Ba 2 Cu 3 O 7 large grain materials [5,6]) is well beyond the saturation magnetization of conventional ferromagnets. This makes them extremely promising as a competing technology for traditional permanent magnets in various applications [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The intermetallic material is more attractive for the next generation of superconducting applications because of the lack of weak-links at the grain boundaries and a high critical transition temperature of 39 K as compared to the conventional NbTi. The superconducting transition temperature of MgB2 is significantly lower than that of YBa2Cu3Oy "Y-123", instead, MgB2 benefits of a high critical current density (Jc) in the polycrystalline state, which makes these materials promising candidates for several industrial applications including the next generation of super-magnets for medical devices, electrical power system, transportation and powerful super-magnets operating at around 20 K [3][4][5][6][7][8][9]. For superconducting super-magnet applications, it is required to produce good quality, low cost MgB2 material with high Jc and an acceptable mechanical performance.…”
Section: Introductionmentioning
confidence: 99%